Annotated species list of Ophiuroidea (Echinodermata) from the Persian Gulf and Gulf of Oman, with new records - Fatemi, Yaser; Stöhr, Sabine (Zootaxa, 2019)
Published records on the Ophiuroidea fauna of the Persian Gulf and Gulf of Oman are scattered in difficult to access journals and books. This study presents a compilation of all published records, complemented with data from new samples. Distribution, habitat and depth in the study area, as well as known Indian Ocean distributions, are included. The taxonomic status of all species was evaluated, critical comments were added as applicable, and several previous records were reassigned to other species. Ophiocoma erinaceus was removed from the fauna of the Persian Gulf and Gulf of Oman, because the only published record was instead Ophiocoma schoenleinii. Previous studies assumed that 46 species of brittle star were known from the study area, but only 38 species were confirmed by this re-assessment, including two new records (Ophiothrix (Ophiothrix) foveolata and Ophiocomella sexradia). Diagnostic features are supplied for difficult to distinguish species. Five species (Macrophiothrix elongata, Amphiura fasciata, Amphiura (Ophiopeltis) hexactis, Amphioplus echinulatus, and Amphioplus seminudus) are so far worldwide known only from the Persian Gulf area. A hexamerous, fissiparous species of Ophiothela that does not concur with any known species was found and may represent a new species. All newly collected species are illustrated with photographs.